Case Study of Utilization of Moringa Leaves in Adonara NTT Using Impact Business Model Canvas - Benedicta Evienia Prabawanti; Ernestus Florian Lamaile (School of Business, IPB University (SB-IPB), 2022)
Indonesia is one of the big countries that have abundant natural wealth. Various kinds of plants in Indonesia show that the natural wealth that exists is a producer of oxygen, minerals, vitamins, and other nutritional content needed by the human body, such as vegetables and fruits. However, behind all this wealth, according to UNICEF, Indonesia is currently facing the problem of malnutrition in which more than two million children are malnourished, and more than seven million children are stunted. This makes Indonesia one of the countries with the highest child stunting burden in the world. NTT is one part of Eastern Indonesia that is poor and has malnutrition problems. The purpose of this study was to conduct a preliminary analysis for a social entrepreneurship project by utilizing the Moringa plant that thrives in Adonara. The results of the analysis can be used as a way to overcome the problems of poverty and malnutrition through the development of social entrepreneurship. The research question posed in the study is how can IBMC analysis be used to assist in running the AMAINA social entrepreneurship project? This research is qualitative research, starting with observing environmental conditions in Adonara, then compiling questions as guidelines for conducting interviews with local residents regarding their knowledge of moringa leaf forgiveness, community empowerment, and household economic improvement. The results of this preliminary study found that the results of the IBMC analysis, financial analysis, and marketing analysis that have been carried out indicate that the AMAINA social entrepreneurship project is feasible to be developed. Keywords: social business model canvas, social enterprises, moringa plants